Menelusuri Dunia Pelayanan Kesehatan dalam Budaya Organisasi: Systematic Literature Review - Suyatno, Endi; Tukiran, Martinus (International Journal of Social and Management Studies, 2024)
The amount of employee involvement in implementing values ​​and assumptions is part of the strength of an organizational culture so that organizational culture can be used as a competitive advantage that is more difficult for other organizations to imitate because success in the organization is greatly influenced by employee performance. Therefore, it is very important to carry out continuous learning in order to form a good culture for the organization. Organizational culture is important in understanding the behavior of people in organizations when managing external demands and internal social change. There has been an increasing push to understand and address organizational culture and try to change it where optimal health performance is hindered. Less attention has been paid to the health care environment and how it can influence individual and organizational outcomes. Before attempting to implement a redesign or new health care reform, it is important to be aware of what characterizes their organizational culture. This research aims to assess the extent of the role of organizational culture in influencing health services. Methods: Searches were conducted in the Emerald, Ebsco-Host, Google Scholar, PubMed and Science-Direct databases for the time period 2008-2018. The research question guiding this review was posed as: “How is it important to study organizational culture in health care settings”. Studies that did not meet the predetermined criteria were excluded, while those that met the inclusion criteria were listed and reviewed further. Twenty-one articles were included in the final analysis of this study. Results: Diverse health care settings were represented in the study. Twenty-one articles were included in the final analysis of this study. Among the relevant studies, 17 were research articles; 12 were quantitative studies, 2 were qualitative, one was a mixed methods study and 2 were articles on the design of organizational culture measurement tools. Conclusion: Excellence in health care delivery is associated with a positive value system delivered through a multidisciplinary team approach and the use of strategic engagement, the most important influence of organizational culture for optimal efficiency in the delivery of quality care. The future use of this organizational culture assessment is in health care studies that seek to understand the health care system in depth and its influence on clinical performance, which will play an important role in achieving planned targets.